Dystocia Due to Hydrocephalic Teratology through Mutational Operations in a Cross-Bred Jersey Cow - Bhathra, Nagarajakumar Revathy; Gupta, Chhavi; Prabaharan, Vaiyapuri; Ganesan, Ajevar; Sabarinathan, Akambaram (The Indian Journal of Animal Reproduction, 2025)
Hydrocephalus is a dropsical condition with the accu mulation of fluid in cranium as a result of an imbalance between the formation and drainage of cerebrospinal fluid (CSF) either in the ventricular system or subarachnoid space characterized by marked enlargement of the cra nium (Noakes et al., 2009). The condition may be caused by environmental influences during fetal development or genetic predisposition of simple autosomal recessive gene with incomplete penetrance (Jackson, 2004) or acquired by in-utero viral infections such as Bovine viral diarrhoea (Agerholm et al., 2015). Other predisposing factors for this malformation may include deficiency of vitamin-A or any other brain lesions that may cause a disturbance in the cerebrospinal fluid dynamics (Ferris et al., 2011). Jubb and Kennedy (1970) stated that congenital hydrocephalus is known to be inherited in cattle and exacerbated its man ifestation by a coexisting hypovitaminosis-A. Death of the fetus is due to pressure on vital centres of the brain. The frontal, temporal and parietal bones are usually involved becoming deformed, separated and thin resulting in improper sculpturing of cranial vault (Purohit et al., 2012). The condition does not affect foetal development but may result in death of the foetus at birth or soon after birth. The present case reports successful per-vaginal delivery of hydrocephalus foetus after relieving fluid from enlarged head through mutational operations.